The Correlation of Audio-visual Media with Student Learning Outcomes - Zulva Rojauna; Muhammad Arif Setiabudi (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2023)
Â The purpose of this research is to define the extent of the relationship between audiovisual means and the results of teaching students to teach Arabic to first-grade students at the Islamic High School "Al Washoya" Kertorejo Ngoro Jombang.Â  As for the results of the research, we can summarize are: (1) the result between an audiovisual means in teaching Arabic to first-grade students at the Islamic High School "Al Washoya" Kertorejo Ngoro Jombang. is average good. (2) The result of the students' teaching of teaching Arabic to first-grade students at the National Islamic High School "Al Washoya" Kertorejo Ngoro Jombang. is a good average. (3) There is no relationship between the audiovisual medium and the results of teaching students in teaching Arabic to first-grade students at the Islamic High School "Al Washoya" Kertorejo Ngoro Jombang. for them and this depends on the results of spss using analysis (Product Moment). From this analysis it is known that the value is 0,338 which means that the value is more than 0.05, so it can be concluded that the null hypothesis H0 agreed and the alternative hypothesis HA is rejectedÂ